Taxonomic review of the pipefish genus Pseudophallus Herald, with the description of a new species (Syngnathiformes: Syngnathidae) - Dallevo-Gomes, Caio I. A.; Mattox, George M. T.; Toledo-Piza, Mônica (Zootaxa, 2020)
We present a taxonomic review of the genus Pseudophallus, based on morphological characters, originally described to include two freshwater pipefish species from the Pacific coastal drainages of the neotropics: P. starksii and P. elcapitanensis, with the later addition of P. mindii, described from Atlantic coastal drainages. Pseudophallus mindii was formerly recognized as a single species ranging from the Brazilian state of São Paulo to Belize in Central America. Five species are recognized in the present study: P. elcapitanensis and P. starksii from the Pacific drainages; P. mindii and P. brasiliensis, the latter so far considered a junior synonym of P. mindii, and a new species. Pseudophallus mindii is redefined to include specimens with higher meristic values and narrow range of variation compared to P. brasiliensis and is restricted to the northern coastal drainages from Venezuela to Central America including the Caribbean region. Pseudophallus brasiliensis is revalidated and occurs from the drainages east of the mouth of the Orinoco to southern Brazil. The new species, Pseudophallus galadrielae sp. nov. is endemic to Lago Izabal in Guatemala. An updated identification key to the currently recognized species is provided.